Prospects of legislative regulation in the sphere of state veteran policy - Sotska , Alla; Chorna , Viktoriia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2026)
The article is devoted to the analysis of the draft Code of Ukraine on the Protection of Statehood, Independence, and the Status of Defenders of the State (reg. № 14265-1). The relevance of the study is due to the growing number of war veterans in the context of armed aggression against Ukraine and the need to create an effective regulatory and legal mechanism to ensure their legal status and social and legal protection. It is emphasized that the legislative framework is the basis for public administration in the field of veteran policy, as it defines key guarantees, support mechanisms, and approaches to assessing the contribution of veterans to the defense of the state. The paper provides a critical analysis of the conceptual foundations and content of Draft Code № 14265-1. The controversy surrounding the codification of state veteran policy as a homogeneous sphere of social relations, which contradicts the essence of codification, has been substantiated. A number of shortcomings have been identified, including excessive detail in provisions that should be regulated by subordinate legislation, legal uncertainty, non-compliance with the requirements of regulatory drafting techniques, and unclear wording. The problematic aspects of determining the legal status of veterans and their families, restrictions on existing social guarantees, the introduction of a three-year «recovery period», and the narrowing of the scope of state obligations to ensure the rights of veterans are analyzed. Particular attention is paid to the risks of a discriminatory approach to the provision of state support depending on financial and property status, the exclusion of certain categories of persons from the veteran policy system, etc. It is concluded that Draft Code № 14265-1, in its proposed form, does not provide an adequate level of legal protection for veterans and requires substantial revision, taking into account the principles of legal certainty, stability of legislation, and state guarantees of the rights of veterans. The purpose of the scientific article is to determine the prospects for legislative regulation of state veterans’ policy in Ukraine, analyze the existing regulatory framework and develop proposals for its improvement, taking into account international experience, as well as modern socio-economic challenges. This study aims to create theoretical and practical recommendations for the formation of an effective state policy of support for veterans, which will contribute to the improvement of their social, economic and legal situation, as well as to increase the level of integration of veterans into society. The research methodology is based on a combination of general scientific and special methods that allow for a comprehensive study of the problem of state veterans’ policy. In particular, the methods used in the work include: analysis of regulatory acts - a detailed analysis of existing laws, resolutions of the Cabinet of Ministers of Ukraine, by-laws and international treaties regulating issues of veterans’ policy in Ukraine, in order to identify gaps and contradictions in legal regulation. Comparative legal method – comparison of the national legal system with the international experience of other countries regarding the legislative provision of veterans’ rights, which will allow identifying best practices and adapting them to Ukrainian realities. Historical and legal method – study of the evolution of state policy on supporting veterans in Ukraine, noting the stages of development of legislation and the influence of social and political processes on this area. Systemic approach – study of state veterans’ policy as a complex socio-legal mechanism, which includes the interaction of state bodies, social institutions and veterans themselves, and determining the role of each element in the overall system. Data analysis – use of statistical and empirical data to analyze the effectiveness of existing veterans’ support programs and identify the main problems that need to be solved. Forecasting and model forecasting – based on the results obtained, building models that allow predicting the effectiveness of future changes in the legislative regulation of state veterans’ policy, as well as assessing the possible social, economic and legal consequences of implementing certain initiatives.